Postoperative radiochemotherapy with weekly cisplatin in patients with head and neck cancer single-institution outcome analysis - Pala, M; Odrazka, K; Holeckova, P; Vitek, P; Kubes, J; Podlesak, T; Klozar, J; Petruzelka, L (Neoplasma, 2012)
The objective of this study was to evaluate the feasibility, toxicity and efficacy of postoperative radiochemotherapy with weekly cisplatin in locoregionally advanced or high risk head and neck cancer in a single institutional setting. Patients with head and neck cancer of stage III/IV or patients with insufficient margins of resection were included in the study. Radiotherapy consisted of 70 Gy/ 7 weeks/ 35 fraction after R1/2 resection and 60-64 Gy/ 6-6,5 weeks/ 30-32 fraction after R0 resection, respectively. All patients received concurrent cisplatin 40 mg/m2 weekly. Between 7/2002 and 12/2008, 100 consecutive patients [WHO ≤ 2, male to female ratio 84/16, median age 54 years] were treated. Tumors of the oropharynx were the most frequent (49%) and stage IV was predominant (86%). 96% patients received the full radiation treatment as planned, median total tumor dose was 66 Gy. Omission of weekly cisplatin had been occurring frequently, the most frequent reason for its early cessation were hematological toxicities (34%). Grade 3/4 mucosal toxicity developed in 32%. No death was observed during the treatment. The late toxicities were acceptable, predominantly subcutaneous fibrosis and xerostomia in most of the cases. We recorded six cases of osteonecrosis. Two and half year overall survival, locoregional control, time to progression and disease free survival were 64%, 88%, 79% and 59%, respectively. Postoperative radiochemotherapy with weekly cisplatin is toxic, but tolerable and highly effective in terms of locoregional control and survival. Multivariete analysis revealed that the only prognostic factor for survival was primary surgery at the University centre.
Keywords: výsledek terapie; Postoperative Care; Male; protinádorové látky; Survival Rate; lokální recidiva nádoru; následné studie; Neoplasm Staging; frakcionace dávky záření; Adult; nádory hlavy a krku; Aged; dospělí; Head and Neck Neoplasms; mužské pohlaví; senioři; Antineoplastic Agents; Dose Fractionation, Radiation; Follow-Up Studies; Treatment Outcome; Neoplasm Recurrence, Local; lidé; ženské pohlaví; Humans; Chemoradiotherapy; pooperační péče; chemoradioterapie; cisplatina; spinocelulární karcinom; Female; Cisplatin; lidé středního věku; staging nádorů; míra přežití; Carcinoma, Squamous Cell; Middle Aged